Liquidity, Leverage And Profitability Ratios As Predictors of Financial Distress With Moderation of Firm Size - Marginingsih, Ratnawaty; Manurung, Adler Haymans; Buchdadi, Agung Dharmawan; Yusuf, Muhammad (Journal of Industrial Engineering & Management Research, 2024)
Companies are often faced with various challenges that can affect their financial condition, one of which is financial distress. In recent years, many retail companies have experienced challenges, including changes in consumer behaviour, intense competition, poor management, high operating costs and poor macroeconomic conditions. The purpose of this study is to explore the role of liquidity, leverage, and profitability ratios as predictors of financial distress by considering moderation of company size. This study uses quantitative causality method. This research focuses on retail companies listed on the Indonesia Stock Exchange in 2018-2022. The type of data used in this study is secondary data. Data obtained from financial reports and annual reports 2018-2022 which are accessed through the Indonesia Stock Exchange. Sampling using purposive sampling method. The results of data processing conducted by researchers were tested using moderated regression analysis (MRA) with the IBM SPSS Statistics version 27 application. The results showed that liquidity and profitability had a negative and significant effect on financial distress. While the leverage variable has a significant positive effect on financial distress. Company size is not able to moderate liquidity and leverage on financial distress. While company size is able to moderate profitabiliats on financial distress.